Adaptive regulation of virulence genes by microRNA‐like RNAs in Valsa mali. Issue 3 (3rd May 2020) - Xu, Ming; Guo, Yan; Tian, Runze; Gao, Chen; Guo, Feiran; Voegele, Ralf T.; Bao, Jiyuan; Li, Chenjing; Jia, Conghui; Feng, Hao; Huang, Lili
Summary: MicroRNAs play important roles in the regulation of gene expression in plants and animals. However, little information is known about the action mechanism and function of fungal microRNA‐like RNAs (milRNAs). In this study, combining deep sequencing, molecular and histological assays, milRNAs and their targets in the phytopathogenic fungus Valsa mali were isolated and identified. A critical milRNA, Vm ‐milR16, was identified to adaptively regulate the expression of virulence genes. Fourteen isolated milRNAs showed high expression abundance. Based on the assessment of a pathogenicity function of these milRNAs, Vm ‐milR16 was found to be a critical milRNA in V. mali by regulating sucrose non‐fermenting 1 ( VmSNF1 ), 4, 5 ‐ DOPA dioxygenase extradiol ( VmDODA ), and a hypothetical protein ( VmHy1 ). During V. mali infection, Vm ‐milR16 is downregulated, while its targets are upregulated. Overexpression of Vm ‐milR16, but not mutated Vm ‐milR16, significantly reduces the expression of targets and virulence of V. mali . Furthermore, deletion of VmSNF1, VmDODA and VmHy1 significantly reduce virulence of V. mali . All three targets seem to be essential for oxidative stress response and VmSNF1 is required for expression of pectinase genes during V. mali –host interaction. Our results demonstrate Vm ‐milRNAs contributing to the infection of V. mali on apple trees by adaptively regulating virulence genes.